LEGAL PROTECTION AGAINST VICTIMS OF DOXING CRIME IN INDONESIA - Achmad, Deni; Farid, Muhammad; Januarti, Rasti Putri; Syavira, Alyfia (Jurnal Bina Mulia Hukum, 2023)
The development of the digital era has increased the number of crimes in cyberspace, one of which is doxing. Doxing is the dissemination of information regarding the personal data of a person or group, which is carried out online without the consent of the party concerned. This act is regulated in Article 26 of Law Number 19 of 2016 concerning Electronic Information and Transactions. Legal protection against the crime of doxing is divided into two, namely preventive and repressive. Preventive is where legal protection is provided to prevent doxing by limiting activities on social media, while repressive is in the form of legal protection in the form of criminal sanctions that have been regulated and the rules that have been established in Indonesia. This research is a legal analysis with a conceptual approach. The main objective of this research was to analyze the legal protection against victims of doxing crime in Indonesia. According to this research Legal protection efforts for victims of doxing crime are divided into 2 (two): Preventive legal protection and Repressive Legal is provided by the government by creating cyber police.